The relationship between anxiety and sleep quality among medical students during Covid-19 pandemic - Yolanda Salim; Surilena; Nelly Tina Widjaja; Fransisca Tjhay (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: Coronavirus disease 2019 (COVID-19) pandemic causes individuals at risk of anxiety and sleep disorders. Anxiety can cause a person’s sleep quality to be poor.Objective: To investigate the association between anxiety and sleep quality among students in the Faculty of Medicine and Health Sciences UNIKA Atma Jaya during the COVID-19 pandemic.Methods: This cross-sectional study involved 635 preclinical and clinical students at FKIK UNIKA Atma Jaya. Measuring instruments used were the Generalised Anxiety Disorder 7 (GAD-7) and the Pittsburgh Sleep Quality Index (PSQI). Both instruments were distributed using Google Forms. Data analysis was performed descriptively and bivariate (Mann Whitney U Test).Results: There were 62% of respondents with anxiety; among them, 37% were mild anxiety; 16.9% were moderate anxious; 8.2% were severe anxiety. This study finds that 66.28% of women with anxiety and 62.8% with poor sleep quality. In 2020, 73.81% of preclinical respondents experienced anxiety and 69.84% experienced poor sleep quality. The bivariate analysis demonstrated a significant association between anxiety and sleep quality among preclinical and clinical students at FKIK UNIKA Atma Jaya during the COVID-19 pandemic (p<0.05).Conclusion: There is an association between anxiety and sleep quality in preclinical and clinical students in FKIK UNIKA Atma Jaya During the COVID-19 Pandemic.